1986
DOI: 10.1073/pnas.83.20.7932
|View full text |Cite
|
Sign up to set email alerts
|

Evidence suggesting that the direct growth-promoting effect of growth hormone on cartilage in vivo is mediated by local production of somatomedin.

Abstract: We have used a catheterization system that permits chronic infusion into the arterial supply of one hindlimb of rats to study the direct effects of rat growth hormone and human somatomedin C on growth of the tibial epiphyseal cartilage plate in hypophysectomized rats. Rat growth hormone (0.4 ,.g per day) or human somatomedin C (0.25, 1, or 4 ,ug per day) stimulated growth of the epiphyseal plate of the infused limb but not of that of the contralateral noninfused limb. The somatomedin C had a dose-related effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(129 citation statements)
references
References 34 publications
4
125
0
Order By: Relevance
“…Since the Cys 78 -Arg mutation in the putative IGFBP domain of WISP3 partially abolishes WISP3 function in chondrocytes, it is conceivable that WISP3 may act, in part, by augmenting the effects of IGFs. IGF-1-mediated up-regulation of cartilage ECM synthesis has already been reported by investigators at several laboratories (30)(31)(32). In addition, preliminary experimental results have demonstrated that an anti-IGF-1 neutralizing antibody partially blocks WISP3-mediated up-regulation of COL2A1 mRNA in C-28/I2 cells.…”
Section: Discussionmentioning
confidence: 53%
“…Since the Cys 78 -Arg mutation in the putative IGFBP domain of WISP3 partially abolishes WISP3 function in chondrocytes, it is conceivable that WISP3 may act, in part, by augmenting the effects of IGFs. IGF-1-mediated up-regulation of cartilage ECM synthesis has already been reported by investigators at several laboratories (30)(31)(32). In addition, preliminary experimental results have demonstrated that an anti-IGF-1 neutralizing antibody partially blocks WISP3-mediated up-regulation of COL2A1 mRNA in C-28/I2 cells.…”
Section: Discussionmentioning
confidence: 53%
“…3B, left) cultures, indicating that the need for each growth factor in chondrocytes is governed by differential mechanisms. The final growth factor concentrations in waste media measured in all of the groups were higher than those added to fresh media, suggesting that chondrocytes possess the ability to secrete endogenous IGF-1 28,29 and TGF-b 30,31 for selfsupplementation such that their desire for exogenous growth factors gradually decreases. It has also been demonstrated that both IGF-1 and TGF-b are shear-responsive factors, meaning their expression and synthesis can be promoted by fluid shear stress.…”
Section: Discussionmentioning
confidence: 98%
“…To date, bovine research in this area has been focused on the association between rbGH and IGF-I primarily as a result of observations from other species which implicated IGF-I as the key mediator of GH action (Isaksson et al 1985;Schlechter et al 1986). …”
Section: Effects Of Growth Hormone On Body Conditionmentioning
confidence: 99%